THE INFLUENCE OF THE CODE OF ETHICS AND CODE OF CONDUCT ON PREVENTING CORRUPTIVE BEHAVIOR IN EMPLOYEES OF THE CORRUPTION ERADICATION COMMISSION OF THE REPUBLIC OF INDONESIA (KPK RI) - Alfret J. Tilukay; Basir; Chryshnanda Dwilaksana (International Journal of Innovative Technologies in Social Science, 2022)
This study discusses the influence of the Code of Ethics and Code of Conduct for KPK personnel which includes 5 (five) basic values, namely: integrity, synergy, fairness, leadership, and professionalism towards preventing corrupt behavior among KPK employees. Integrity, synergy, fairness, and leadership are placed as independent/exogenous variables while professionalism is placed as a moderating variable. The research objective is to answer the formulation of the problem which includes 9 research questions. The research method uses a quantitative approach through SEM (Structural Equation Model) analysis. The number of samples was 321 people who were calculated based on the Slovin formula and were taken using a proportionate random sampling technique, in this case, the KPK employees who came from State Civil and Assigned Civil Servants. Variable operationalization uses indicators that have been formulated in the Code of Ethics and Code of Conduct for KPK Employees, namely as stated in Perdewas KPK Number 2 of 2021, and from various theories. From the results of the study, it was concluded that there is a positive and significant influence of Integrity, Synergy, and Leadership variables on Professionalism and Prevention of Corrupt Behavior among Employees at the KPK. The justice variable was found to have no significant effect. This means that if the quality of the three variables that have had this influence is improved, it will be followed by an increase in professionalism and prevention of corrupt behavior. Fundamental improvements are needed regarding aspects of justice, which include the creation of a conducive work environment and perceptions of fairness in the fulfillment of employee welfare to improve the variables of justice.